A Comparative Study of the Thoughts of Spinoza and Iqbal on Freedom, Predestination, and Human Agency with Emphasis on the Light of Quranic Thought - Kareem, Ata ul; Nazia, Uzma Zareen (Pakistan Languages and Humanities Review, 2025)
This comparative analysis looks at the philosophical approach of Baruch Spinoza and Muhammad Iqbal on freedom, destiny and human agency especially in quorum about the Quranic thought. The opinions of both the philosophers are explained in both rational and metaphorical terms to enable the reader be able to make a better decision on what opinion is right and wrong. Although the works of the two are now in different historical and cultural settings, there is a close relationship between the will of God and the autonomy of the human beings in the works of both thinkers. Criticizing this deterministic approach, Spinoza has affirmed that freedom can be explained as a sense of necessity through rational comprehension, whereas Iqbal - with the help of Islamic traditions - has promoted a dynamic definition of freedom, which has self-determination, moral action and growth of personal connectivity with God. This paper examines the tensions between metaphysical materialism of Spinoza and the God-based self-knowledge of Iqbal, with the regard to identifying main areas of agreement and what restrictions there are to them, especially in terms of individual freedom versus divine omniscience. By placing their perceptions in context within discourse of the Quran, the comparative study in question asserts that as opposed to Spinoza, who emphasizes freedom as something characterized by necessity, Iqbal argues that the freedom should be acquired through active involvement and accountability.